Manajemen Pengorganisasian Program Bahasa Arab di Pondok Pesantren Salaf - Fitri Hidayati; Zakiyah Arifah; Ainun Jariyah; Shofiatus Zahriyah (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2019)
Organizing is the second step in the management of the organization after planning. Proper planning will not run correctly, without no one to run and move it, without clearing the job and who will do it. That is the essence of the organizing. Good organizing will produce the right organization, from the work system, structure, resources, and other aspects. This study discusses 1) organizing management in Arabic program pesantrens, 2)job description in Arabic program pesantrens. This study was descriptive qualitative research. The data are collected through interviews, observation, and documentation. Then the data were analyzed in three steps, 1) data reduction, 2) data presentation, 3) concluding/ verification. The results of this research shows that 1) the organizing management Arabic program in pesantren is using a coordination with staff department it can be seen from the manager's task under the chairman, after coordinating with the staff (departmental coordination), and on each program in the Arabic department because in Arabic and organization programs generally have a model line structure and staff (line and staff organization). 2)Division of task the management board recruits service people, student alumni, teacher, or lecturers who are in charge of the foundation. The board on the Arabic program get responsibility and authority on the organization system in the Arabic program.